2010
DOI: 10.1016/j.ica.2009.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterisation of isomeric cycloaurated complexes derived from the iminophosphorane Ph3PNC(O)Ph

Abstract: Using different organomercury substrates, two isomeric cycloaurated complexes derived from the stabilised iminophosphorane Ph 3 P=NC(O)Ph were prepared. Reaction of Ph 3 P=NC(O)Ph with PhCH 2 Mn(CO) 5 gave the manganated precursor (CO) 4 Mn(2-C 6 H 4 C(O)N=PPh 3), metallated on the C(O)Ph substituent, which yielded the organomercury complex ClHg(2-C 6 H 4 C(O)N=PPh 3) by reaction with HgCl 2 in methanol. Transmetallation of the mercurated derivative with Me 4 N[AuCl 4 ] gave the cycloaurated iminophosphorane A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…This is as expected from related compounds that have been structurally characterised [23,24]. This ready synthesis of the mercury derivative of naphthalimide provides a substrate for the many different syntheses that are established based on aryl-mercury compounds [25], giving many potential 2-substituted naphthalimide compounds.…”
Section: Reaction With Hgclsupporting
confidence: 56%
“…This is as expected from related compounds that have been structurally characterised [23,24]. This ready synthesis of the mercury derivative of naphthalimide provides a substrate for the many different syntheses that are established based on aryl-mercury compounds [25], giving many potential 2-substituted naphthalimide compounds.…”
Section: Reaction With Hgclsupporting
confidence: 56%
“…We followed the strategy for the preparation of Hg(Ph 3 P=N-CO-2-C 6 H 4 )Cl. 53 The C–H activation at the N-CO-Ph fragments takes place at a manganese center, and by transmetalation of the resulting cyclometalated iminophosphorane manganese compounds to HgCl 2 , the organomercury derivatives with PPh 3 [Hg(Ph 3 P=N-CO-2-C 6 H 4 )Cl] 53 or water-soluble phosphine PTA [Hg(PTA=N-CO-2-C 6 H 4 )Cl] ( 7 ) are obtained in high yields. Transmetalation reactions of [Hg(Ph 3 P=N-CO-2-C 6 H 4 )Cl] 53 and 7 with [(η 6 - p -cymene)Ru(μ-Cl)Cl] 2 afford new cyclometalated compounds [(η 6 - p -cymene)Ru(IM-k-C,N)Cl] (IM = Ph 3 P=N-CO-2-C 6 H 4 8 ; PTA=N-CO-2-C 6 H 4 9 ) in high yields (Scheme 2 ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Solvents were purified by use of a PureSolv purification unit from Innovative Technology, Inc. Compounds [PhCH 2 Mn(CO) 5 ], 79 [(η 6 - p -cymene)Ru(μ-Cl)Cl] 2, 52 [Hg(2-C 6 H 4 C(O)N=PPh 3 )Cl], 53 and IM ligands Ph 3 P=N-CO-2-N-C 5 H 4 , 51 Ph 3 P=N-8-C 9 H 6 N, 49 [Cp-P(Ph 2 )=N–CH 2 -2-NC 5 H 4 }Fe(Cp)], 48 and Ph 3 P=N-CO-2-C 6 H 4 51 were prepared by reported methods. The purity of the compounds, based on elemental analysis, is ≥99.5%.…”
Section: Methodsmentioning
confidence: 99%
“…Azides are notorious for their explosive nature, but as the percentage of nitrogen in the azide decreases they become less explosive. The Smith rule [11] is an indication of whether an [30]. The phosphine was reacted with an azide to produce an intermediate mercurated iminophosphorane, which could be transmetalated with Au(III).…”
Section: Complexes Of Glycosyl Iminophosphoranesmentioning
confidence: 99%
“…Monitoring of the reaction by 31 P NMR and ESI-MS showed that the intermediate mercurated iminophosphorane, 5a, had fully formed after 1.5 h. Removal of the solvent gave 5a which was used directly, after characterisation by 31 P NMR and ESI-MS. The ion [AuCl 4 ] À has been used to produce gold(III) iminophosphoranes [6,17,30]. To 5a was added [NMe 4 ][AuCl 4 ] and dry acetonitrile and the mixture stirred for several days in the dark.…”
Section: Complexes Of Glycosyl Iminophosphoranesmentioning
confidence: 99%